Influence of Concentration and Agitation of Sodium Hypochlorite and Peracetic Acid Solutions on Tissue Dissolution - Tanomaru-Filho, Mário [UNESP]; Silveira, Bruna Ramos Franco [UNESP]; Martelo, Roberta Bosso [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Jaypee Brothers Medical Publishing, 2015)
AIM AND OBJECTIVE: To evaluated the tissue dissolution of sodium hypochlorite (NaOCl) and peracetic acid (PA) solutions at different concentrations, with or without ultrasonic agitation. MATERIALS AND METHODS: The following solutions were analyzed: 2.5% NaOCl, 0.5, 1 and 2% PA, 1% PA associated with 6.5% hydrogen peroxide (HP) and saline. Fragments of bovine pulp tissue with 25 ± 2g mg were immersed into test tubes containing 4 mL of the solutions for 10 minutes. In the groups with agitation, pulp tissues were submitted to 2 cycles of 1 minute of ultrasonic agitation. The specimens were weighed after the removal from the solutions. The percentage of mass loss was calculated according to the difference of mass before and after exposure to solutions. Data were submitted to ANOVA and Tukey tests (p < 0.05). RESULTS: A total of 2.5% NaOCl with or without agitation showed the higher tissue dissolution (between 64.5 and 67% of mass reduction) (p < 0.005). By comparing the PA solutions, the concentrations of 1 and 2% with or without agitation and the concentration of 0.5% with agitation showed similar dissolution activity (between 35.4 and 44% of mass reduction). The use of the ultrasonic agitation promoted an increase of the dissolution ability only for 0.5% PA. CONCLUSION: Peracetic acid solution has pulp tissue dissolution. However, this ability is lower than 2.5% NaOCl solution. CLINICAL SIGNIFICANCE: The sodium hypochlorite solution shows higher ability to dissolve tissue than PA.
Keywords: Dental pulp; Irrigating solution; Root canal treatment